Two-channel two-transceiver IEEE 802.16 wireless backhaul - Chai, P.; Chung, Kah-Seng; Chan, King-Sun (2011)
An IEEE 802.16 wireless backhaul network is a cost effective, easier to deploy, and readily scalable solution to deliver broadband communication services from gateway nodes located in regional or metropolitan centres to less densely populated remote rural communities. In order to ensure the network remains operational even under a node or link failure, extra nodes and links are incorporated to provide alternative paths for rerouting traffic. In addition, nodes located within the interference range are assigned with different frequency channels to allow them to transmit simultaneously without causing transmission collisions. In this paper, a two-channel two-transceiver distributed channel assignment (TTDCA) algorithm is proposed to allocate minislots and frequency channels to the nodes in a failure tolerant IEEE 802.16 wireless backhaul network. Computer simulation results show that the TTDCA algorithm is effective in significantly improving the throughput and delay performance of the network, making it suitable not only to support large amount of data traffic but also for transporting delay-sensitive traffics.